Assessment of municipal waste management systems using performance indicators to analyze recycling capacity the case study of Corumbataí basin, São Paulo state, Brazil - Luz, Fernanda Giffoni Fernandes [UNESP]; Rozenský, Ladislav; Vrba, Zdeněk; Hansen, Justin Michael; Lípa, Jan; Dolista, Josef; Vítek, Martin; Alves De Castro, Marcus César Avezum [UNESP] (My University, 2021)
The analysis of waste management practices is a multidimensional challenge faced by authorities, especially in developing countries, where actions are needed to reduce, reuse and increase recycling. Performance indicators are often used to assess the quality of municipal solid waste management systems. However, some studies suggest that different realities require different indicators to evaluate the quality of management systems. Moreover, effective data on the reality of municipalities are scarce, especially on the work carried out by the informal sector within the waste management systems. The purpose of this study was to investigate a set of indicators in order to examine the recycling modes and capacity of six municipalities in the interior of São Paulo estate in Brazil. Focus was placed on how the collection of the material for recycling is carried out. The analysis revealed that the municipalities have selective collection being carried out in urban areas, but in different ways and not always with the support of the public power. The reality found in this study points to a great participation of the informal collection in the recycling capacity of the cities surveyed.This study estimates approximately 8% of refuse are collected by the informal recycling of the total amount estimated for generation every year in the investigated cities. The average recycling rate in selected cities is 10.8%.
Keywords: Informal sector; Municipal waste management; Recycling; Waste indicators